The Impact of Perceived Organizational Justice on Organizational Commitment with the Mediating Role of Positive Organizational Behavior in the Context of Elementary Schools - Esmaeili Lemjiri, Fatemeh; Alshomar, Al_ Zahra (International Journal of Business Management and Entrepreneurship, 2025)
Abstract Introduction and Objective:Organizations seeking greater effectiveness and goal achievement must pay attention to their human capital and foster a sense of fairness among employees. Recognizing employees’ values and needs plays a key role in enhancing organizational commitment and overall performance. Accordingly, the present study aimed to investigate the effect of organizational justice on organizational commitment, with the mediating role of positive organizational behavior among elementary school principals. Methodology: This research was applied in purpose and descriptive–correlational in design. The statistical population included all elementary school principals in Zahedan city, from whom 112 individuals were selected through proportional stratified and convenience sampling methods. Data were collected using three questionnaires: Organizational Justice, Organizational Commitment, and Positive Organizational Behavior. Content validity was confirmed, and reliability coefficients (Cronbach’s alpha) were obtained as 0.66, 0.61, and 0.75, respectively. Data analysis was conducted using stepwise regression and structural equation modeling (SEM). Results: The findings indicated that organizational justice has a positive and significant effect on the organizational commitment of elementary school principals at a 66% confidence level (P < 0.01). Furthermore, positive organizational behavior was found to play a mediating role between organizational justice and organizational commitment at a 65% confidence level (P < 0.05). Stepwise regression analysis showed that among the components of organizational justice, interactional justice was able to predict organizational commitment, and among the components of positive organizational behavior, self-efficacy was able to predict the organizational. Conclusion: It can be concluded that promoting organizational justice, particularly interactional justice, can enhance principals’ commitment and improve the overall working climate in elementary schools. Therefore, implementing policies and regulations consistent with organizational justice principles can serve as an effective strategy for improving the efficiency of the educational system.